The Effect of CaO and MgO as Expanding Additives to Improve Cement Isolation Strength under HPHT Exposure - Rubi Rubiandini; Septoratno Siregar; Nur Suhascaryo; Deny Efrial (Journal of Engineering and Technological Sciences, 2005)
Cementing is one of the most important parts in oil-well drilling. Recent development in oil-well drilling technology has led to a more problematic case in cementing. High temperature cementing is one of the problems. High temperature cementing may cover steam recovery wells, geothermal wells and ultra deep wells.The use of expanding cements as an effort to improve the sealing efficacy of annulus cementing has been considered for a long time as a promising solution to the existing problems. CaO and MgO have been proposed as two of the most effective additives to create excellent expanding cement.The purpose of this study is to find the effect of adding up burnt pure CaO and MgO to the value of compressive strength and shear bond strength of API class G cement in high pressure and high temperature condition. The method that we used within this research is an evaluation of the data taken from a simulator that simulated within temperature range of 100 "“ 250 oC and pressure of 2000 psi.The conclusion is taken according to the results which saying that the addition of burnt pure CaO and MgO would increase the shear bond strength and the compressive strength on specific condition up to 200 oC temperature. The addition won't be effective for the condition of 250 oC temperature. The behavior of cement strength was also influenced by the length of curing time.Further more, research on expanding cement needs to be developed and extended whether to vary its compositions, temperatures, or curing time conditions. The compatibility when mixed with other additives together with silica flour has not yet been figured out.